Effects of Flow-Diverting Device Oversizing on Hemodynamics Alteration in Cerebral Aneurysms - Mut, F.; Cebral, J.R. (American Journal of Neuroradiology, 2012)
BACKGROUND AND PURPOSE: Flow-diverting devices are increasingly being considered for large or giant aneurysms with wide necks, which are difficult to treat with coils or clips. These devices are often oversized to achieve good positioning against the artery wall. The objective of this study was to analyze the effect of oversized flow-diverting devices in altering aneurysmal flows and creating hemodynamic environments favorable for thrombosis and aneurysm occlusion. MATERIALS AND METHODS: Patient-specific computational fluid dynamics models of 3 cerebral aneurysms were constructed from 3D angiography images. Numeric simulations of the hemodynamics after implanting stents of increasing diameters were performed. The corresponding modifications of hemodynamic variables such as aneurysm inflow rate, average velocity, shear rate, and wall shear stress were calculated and compared. RESULTS: The results indicate that because the devices are oversized, the stent cells stretch in the direction of the vessel axis, change cell angles, and result in larger cells. This change in the cell geometry causes a diminution of the hemodynamic performance of the stent. Quantitatively, stent oversizing results in larger values of aneurysm inflow rates, average velocity, shear rate, and wall shear stress compared with nonoversizing cases. CONCLUSIONS: The efficacy of flow-diverting devices in modifying intra-aneurysmal flow can be substantially reduced by oversizing the devices. As the level of device oversize increases, aneurysmal hemodynamic variables are significantly less affected. CFDcomputational fluid dynamicsFDflow diverter